Discussion on the Formula in ISO 21771: 2007 - Li Qing; Guo Yong (Jixie chuandong)
The analysis and discussion of the calculation formulas in the ISO 21771: 2007（ Gears-Cylindrical involute gears and gear pairs-Concepts and geometry） are carried out,and the contrast and analysis of the formulas in DIN ISO 21771: 2014,ISO 21771: 2007 and DIN 21773: 2014 are carried out. Some suggestions are proposed for the improper parts of the formula,in order to provide reference for standard revision and users.